Sistem Konstitutif Dalam UU No 15 Tahun 2001 Tentang Merek Bagi UMKM - Achmad Fata'al Chuzaibi (Fakultas Hukum, Universitas Islam Bandung, 2011)
Basically, legal protection against trademark is to prevent the act of unfair competition. This can be done by prohibiting another person to commit a breach of trademark law. For this purpose, trademark has been regulated in the Law of the Republic of Indonesia No.15 of 2001 regarding Trademark (referred herewith as Trademark Law). The role of trademark becomes significantly important in protecting industrial rights in intellectual works, maintaining fair competition, and encouraging fair and free trade.Under Trademark Law No. 15 of 2001, trademark registration system is based on constitutive system. Trademark Law No. 15 of 2001 sets out requirements, procedures for registration, registration fee and other proceedings. Based on this system, the trade mark owners have the right of registered trade mark by prohibiting other parties from using it without their permission. The trademark registration system, however, is hard for Small and Medium Size Microenterprise to observe, so that prevent it from registering the trade mark. This article provides an analysis of the challenge of the implementation of , constitutive system under Trademark Law No. 15 of 2001 for Small and Medium Size Microenterprise. The point of this article is to point out that, in the light of the trade mark system, the question of the gap between the Small and Medium Size Microenterprise and big business still remains the problem